2020
DOI: 10.1002/jbm.a.37028
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic poly(2‐acrylamido‐2‐methylpropanesulfonic acid) gel induces chondrogenic differentiation of ATDC5 cells via a novel protein reservoir function

Abstract: We previously demonstrated that a synthetic negatively charged poly(2‐acrylamido‐2‐methylpropanesulfonic acid) (PAMPS) gel induced chondrogenic differentiation of ATDC5 cells. In this study, we clarified the underlying molecular mechanism, in particular, focusing on the events that occurred at the interface between the gel and the cells. Gene expression profiling revealed that the expression of extracellular components was enhanced in the ATDC5 cells that were cultured on the PAMPS gel, suggesting that extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Since transplantation of the C1A1 porous hydrogel alone failed to induce angiogenesis, the C1A1 porous hydrogel was immersed in VEGF, which promotes angiogenesis, and implanted into the mice brains. Accumulation of VEGF into hydrogel was expected as we have already reported the reservoir function of hydrogel for growth factors 46 . To confirm the formation of blood vessels in the implanted C1A1 porous hydrogel, in vivo live imaging using a two-photon microscope was performed, and vascularization was observed inside the gel on day 15 (Fig.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Since transplantation of the C1A1 porous hydrogel alone failed to induce angiogenesis, the C1A1 porous hydrogel was immersed in VEGF, which promotes angiogenesis, and implanted into the mice brains. Accumulation of VEGF into hydrogel was expected as we have already reported the reservoir function of hydrogel for growth factors 46 . To confirm the formation of blood vessels in the implanted C1A1 porous hydrogel, in vivo live imaging using a two-photon microscope was performed, and vascularization was observed inside the gel on day 15 (Fig.…”
Section: Resultsmentioning
confidence: 63%
“…Inflammatory cells such as macrophages/microglia are important for angiogenesis 53 , 54 . Furthermore, hydrogels are used as drug delivery systems 19 ; in fact, we have reported that NaMPS gel has a reservoir function 55 . Thus, the reservoir function of C1A1 porous hydrogels for endogenously secreted growth factors may be involved in angiogenesis, leading to neuronal tissue reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory cells such as macrophages/microglia are important for angiogenesis 50, 51 . Furthermore, hydrogels are used as drug delivery systems 19 ; in fact, we have reported that NaMPS gel has a reservoir function 52 . Thus, the reservoir function of C1A1 porous hydrogels for endogenously secreted growth factors may be involved in angiogenesis, leading to neuronal tissue reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, poly(2‐acrylamido‐2‐methyl‐1‐propanesulfonic acid) (PAMPSA) organic polymer was selected that has a high affinity to NH 3 . It has been used as hydrogels for drug delivery, [ 28 ] and as scaffolds for cartilage regeneration, [ 29 ] and for NH 3 absorption. [ 30 ] Due to the presence of sulfonate functional group (SO 3 − ) in PAMPSA, its electrical resistance is highly dependent on the pH and the presence of other charged or polar species.…”
Section: Introductionmentioning
confidence: 99%